Physical and mechanical characterization of jute fabric composites - Acha, Betiana Andrea (2005)
As-received and washed jute fabrics were used as reinforcement for a thermoset resin. The mild treatments performed on the jute fabrics did not significantly affect their physical and thermal behaviors. The washed fibers absorbed less water than the unmodified (as received) ones, indicating that the coating used to form the fabrics was hygroscopic. Measurements of the fiber mechanical properties showed a high dispersion due to fiber irregularities, although the values obtained were in agreement with data reported in the literature. These results were also analyzed with the Weibull method. To investigate the effect of the jute treatments on the interface properties, impact, compression, and tensile tests were carried out. The composites made from as-received jute had the highest impact energy, which was probably associated with weak interfacial adhesion. Composite samples behaved more ductilely in compression than in tensile situations due to the brittle characteristics of the resin used as matrix. The effect of the orientation of the fibers with respect to the direction of the applied force in the different mechanical tests was also studied.